2002
DOI: 10.1063/1.1497457
|View full text |Cite
|
Sign up to set email alerts
|

Methane conversion into acetylene in a microwave plasma: Optimization of the operating parameters

Abstract: Articles you may be interested inDecomposition of methylene blue in water using a dielectric barrier discharge: Optimization of the operating parameters J. Appl. Phys.Carbon dioxide reforming of methane by pulsed glow discharge at atmospheric pressure: The effect of pulse compression Time of flight secondary ion mass spectroscopy investigation of ultralow-k dielectric modifications in hydrogen and deuterium plasmas

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
47
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 27 publications
2
47
0
3
Order By: Relevance
“…Indeed C x H y hydrocarbons with x > 2 were not found in high quantities in the experiments. [29] CH 3 and C 2 H 2 are generally found to be the abundant diamondforming species under the considered experimental conditions. [25,[30][31][32] It can be clearly observed that at lower temperatures (up to $1200 K) there is not much variation in CH 4 , indicating its non-participation in the deposition process.…”
Section: à9mentioning
confidence: 97%
“…Indeed C x H y hydrocarbons with x > 2 were not found in high quantities in the experiments. [29] CH 3 and C 2 H 2 are generally found to be the abundant diamondforming species under the considered experimental conditions. [25,[30][31][32] It can be clearly observed that at lower temperatures (up to $1200 K) there is not much variation in CH 4 , indicating its non-participation in the deposition process.…”
Section: à9mentioning
confidence: 97%
“…Further on, concentrations of atomic species like H, O, and electron are increased at higher plasma temperature due to higher rate of electron impact ionization and dissociation reactions. Moreover, complex hydrocarbons (like C 2 H 4 , CH 3 OH, C 2 H 6 , CH 2 O, and C 2 H 2 ) reported in ref., [1,5] in our system have very low concentrations, and their probability decreases drastically at higher temperature near our plasma reaction zone. Therefore, regarding these simulations in the CH 4 …”
Section: Pre-estimation To Experiments (Simulation Of Compositions Ofmentioning
confidence: 99%
“…Also, pure CH 4 MW plasma conversion experiments showed the possible existence of C 2 H 2 , C 2 H 4 , C 2 H 6 , and a small amount of C 3 H 6 and C 3 H 8 species in the final product. [5] The species involved in the plasma were selected according to the experimental analysis in ref. [1,5,14] along with our pre-assumption in which we carried out for CH 4 ÀO 2 ÀAr MW plasma reactor.…”
Section: Pre-estimation To Experiments (Simulation Of Compositions Ofmentioning
confidence: 99%
See 2 more Smart Citations